The Impact of the Common Knowledge Construction Model (CKCM) Integrated with Ethnoscience and Podcasts on Science Process Skills in the Topic of Chemical Bonding - Viki Nurlatifah; Mohammad Masykuri; Wirawan Ciptonugroho; Sri Yamtinah; Maria Ulfa; Bakti Mulyani; Agung Nugroho Catur Saputro; Ari Syahidul Shidiq (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2024)
Technological advances and competition in the 21st-century demand that students enhance their knowledge and skills. The Common Knowledge Construction Model (CKCM) can effectively influence students' academic skills and achievements in chemistry. This study examined the impact of CKCM integrated with ethnoscience and podcasts on improving science process skills and student learning outcomes. A quasi-experimental design with cluster random sampling was employed to select experimental and control groups from the population of specialization 11th-grade science program (five classes) in a senior high school in Boyolali Regency. Multiple-choice questions were used to measure science process skills and learning outcomes. Descriptive analysis and hypothesis testing were conducted using the Kruskal-Wallis test. The results revealed a significance value of 0.000 in both hypothesis tests for science process skills and learning outcomes. A significance value of less than 0.05 indicates that the application of CKCM positively impacts both variables. Integrating ethnoscience provides a deeper understanding by building culturally contextualized logical thinking. Supported by podcast media, it creates a dynamic and engaging learning environment that helps students actively construct their knowledge. This research contributes to developing the CKCM learning model mediated by podcasts to empower chemistry knowledge and science process skills, preparing students to meet the challenges of the 21st century.